2009
DOI: 10.1590/s1516-89132009000400028
|View full text |Cite
|
Sign up to set email alerts
|

Microbial succession within an anaerobic sequencing batch biofilm reactor (ASBBR) treating cane vinasse at 55ºC

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
1
11

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 15 publications
0
11
1
11
Order By: Relevance
“…The presence of carbon fibers in the electrodes could lead to high methane production efficiencies by protecting the methanogenic community from high levels of residuals VFA and salts, which may act as stressors (Sasaki et al 2009(Sasaki et al , 2011b. The correlation between a higher methane yield and the higher abundance of Methanosaeta is to be expected, since an OLR of only 2 g COD L -1 d -1 was applied, leading to circumstances that favor Methanosaeta over Methanosarcina , Ribas et al 2009). However, as there was no significant difference in community composition between anode and cathode biofilm, nor was there any difference between the planktonic phase in the different reactors, with or without electrodes, it can be confirmed that there was no effect of the applied cell potential and that biofilm development was the crucial factor to obtain stable methane production.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of carbon fibers in the electrodes could lead to high methane production efficiencies by protecting the methanogenic community from high levels of residuals VFA and salts, which may act as stressors (Sasaki et al 2009(Sasaki et al , 2011b. The correlation between a higher methane yield and the higher abundance of Methanosaeta is to be expected, since an OLR of only 2 g COD L -1 d -1 was applied, leading to circumstances that favor Methanosaeta over Methanosarcina , Ribas et al 2009). However, as there was no significant difference in community composition between anode and cathode biofilm, nor was there any difference between the planktonic phase in the different reactors, with or without electrodes, it can be confirmed that there was no effect of the applied cell potential and that biofilm development was the crucial factor to obtain stable methane production.…”
Section: Discussionmentioning
confidence: 99%
“…Neste cenário alguns estudos, como o de Ribas et al (2009) buscam propor melhores formas de disposição do resíduo no solo agrícola através do seu tratamento prévio.…”
unclassified
“…Las biopelículas microbianas están conformadas por diferentes estratos, cada uno con complejas agrupaciones (Rochex et al, 2009); donde microorganismos pueden ocupar regiones específicas condicionando la estructura de la biopelícula (Tian et al, 2016); además, la estatura y composición de una biopelícula cambia a lo largo del tiempo impulsada por cambios ambientales, disponibilidad de nutrientes y factores intrínsecos a las biopelículas (Ribas et al, 2009;Luria et al, 2016).…”
Section: Discussionunclassified